Associations of premenstrual symptoms with daily rumination and perceived stress and the moderating effects of mindfulness facets on symptom cyclicity in premenstrual syndrome: original article - Nayman, Sibel; Konstantinow, Desiree Tina; Schricker, Isabelle; Reinhard, Iris; Kühner, Christine (Archives of women's mental health, 2023)
Subthreshold premenstrual symptoms can be impairing even if the diagnostic criteria for premenstrual dysphoric disorder (PMDD) are not reached. Previous research suggests shared psychological risk factors without a clear differentiation of premenstrual syndrome (PMS) from PMDD. This study focuses on a sample with a wide range of premenstrual symptoms not reaching PMDD-criteria and aims to investigate within-person associations of premenstrual symptoms with daily rumination and perceived stress during the late luteal phase as well as cycle-phase specific associations of habitual mindfulness including present-moment-awareness and acceptance with premenstrual symptoms and impairment. Fifty-six naturally cycling women with self-reported premenstrual symptoms completed an online diary on premenstrual symptoms, rumination and perceived stress over two consecutive menstrual cycles, and baseline questionnaires on habitual present-moment-awareness and acceptance. Multilevel analyses revealed cycle-related variations in premenstrual symptoms and impairment (all ps < .001). Higher within-person levels of core and secondary premenstrual symptoms during the late luteal phase predicted increased daily rumination and perceived stress (all ps < .001) and increased somatic symptoms predicted increased rumination (p ≤ .018). Higher habitual present-moment-awareness was linked to lower premenstrual symptom and impairment levels toward the late luteal phase whereas higher habitual acceptance was associated with lower premenstrual functional impairment (p ≤ .015). Premenstrual symptom increases during the late luteal phase in women with PMS seem to be linked to increased daily rumination and perceived stress. Trait present-moment-awareness and acceptance in turn seem to reflect protective factors against premenstrual distress and may represent useful targets for interventions.